# Answer on Linear Algebra Question for Matthew Lind

Question #24223

Prove that 0v = 0, for all v in V: I put down: from property 5 and property 8 we know that: v = 1v = (1+0)v = 1v + 0v = v + 0v = v+0 =v. thus, -v+v = -v+(v+0v) = (-v+v) + 0v. He said it was right but not totally right, and to prove it for anything (general case), ,and something about expressing W in terms of v in order to do that. Anyone?

Expert's answer

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment